Humidity Sensor Based on a Hollow Core Fiber Anti-Resonant Reflection Optical Waveguide - Ao Cheng; Chaoqi Wang; Jiadong Xu; Peiqing Zhang; Yu Zheng; Shixun Dai (Photonic Sensors)
Abstract In this paper, a graphene oxide (GO) composite film-coated humidity sensor is proposed based on the hollow core fiber (HCF). A segment of the HCF is spliced between two segments of the single-mode fiber (SMF). The relative humidity (RH) sensing characteristics of the sensor are experimentally investigated by observing the intensity shift of resonant dips in the transmission spectrum, which shows the GO composite film-coated HCF has the good stability in the measurement of humidity. The maximum humidity sensitivity of 0.12 dB/%RH is obtained in the RH range of 30%–78%. The proposed sensor has the advantages of the simple structure, easy fabrication, good stability, and high performance, which can be applied to marine climate detection, tunnel air humidity detection, agricultural testing, and other fields.